Exam Anxiety Among Students: A Gender-Based Study - Minesh Kumar Ghimire; Anima Shrestha; Jagannath Kandel; Kalyan Poudel (Jurnal Hilirisasi Pengabdian Masyarakat, 2025)
Exam anxiety is characterized by intense nervousness, a profound level of fear that hinders the effective application of previously acquired knowledge during a test situation, ultimately leading to a decline in cognitive performance and overall subjective well-being. This study examined the prevalence and gender-based differences in exam anxiety among undergraduate students, utilizing a descriptive design and convenient sampling. Data were collected through an online survey using the Test Anxiety Questionnaire developed by Nist and Diehl. The finding revealed noteworthy gender differences, with females reporting higher levels of both healthy and unhealthy exam anxiety compared to males.  Males exhibited a greater proportion of extremely low anxiety levels. The chi-square test of independence confirmed a statistically significant relationship between gender and anxiety level (p< 0.05), emphasizing gender as a crucial determinant. These outcomes highlight the gender-sensitive mental health interventions tailored to address specific stressors and coping mechanisms, as well as advocating for open discussion.